Development of Cloud-Based Taskify Application For Time Management - Nur Fadhylah As; Muh. Rahmat Wahyudi JY; Annajmi Rauf; Pramudya Asoka Syukur; Andi Dio Nurul Awalia; M. Miftach Fakhri (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
In the 21st century digital era, advances in technology and information have developed rapidly, one of which is cloud computing. This study aims to design a cloud-based task management application called TaskIfy using firebase technology and agile methods. TaskIfy was designed to help users manage their time and daily activities more effectively. The Agile method was used in two sprint cycles to ensure iterative development and responsiveness to user feedback. The main features implemented include authentication, task management, search, and calendars. Black box testing was conducted to ensure the functionality of the application. The results showed that TaskIfy successfully improved user efficiency and productivity in managing schedules and completing tasks. However, some additional features have not been developed, such as better calendar integration and collaboration features. Future research can focus on developing these features to optimize the user experience. The main contribution of this research is the implementation of TaskIfy as a practical tool for effective time management, combining cloud computing technology and agile methodology to improve efficiency in everyday life.